Una mirada desde el siglo XXI a la estética contemporánea de la violencia de género: (reflexiones desde el género) - Hernandez Palma, Oona (Corporación Universitaria Americana, 2022)
Violence - as distinct from power - always seeks instruments for its existence. Hobbes' old phrase is interesting to guide our reflections on contemporaneity: "Covenants without coercive measures are nothing but words". The Second World War was not followed by a period of peace, but by the Cold War and the establishment of a military-industrial complex (Arendt, 1970). Karl Marx (2010) in the 18th Brumaire of Louis Bonaparte stated that historical events occur twice in history: once as tragedy and the second time as farce.